Common Bias and Challenges in Physical and Rehabilitation Medicine Research: How to Tackle Them - Thibaut, Aurore; Beaudart, Charlotte; Martens, Géraldine; Bornheim, Stephen; Kaux, Jean-François (Frontiers in Rehabilitation Sciences, 2022)
The importance of evidence-based medicine is crucial, especially in physical and rehabilitation medicine (PRM), where there is a need to conduct rigorous experimental protocols, as in any medical field. Currently, in clinical practice, therapeutic approaches are often based on empirical data rather than evidence-based medicine. However, the field of PRM faces several challenges that may complicate scientific research. In addition, there is often a lack of appropriate research training in educational programs. In this context, we aim to review the methodological challenges in PRM and provide clear examples for each of them as well as potential solutions when possible. This article will cover the following themes: 1. Choosing the right study design and conducting randomized and benchmarking controlled trials; 2. Selecting the appropriate controlled, placebo or sham condition and the issue of blinding in non-pharmacological trials; 3. The impact of populations’ heterogeneity and multi-comorbidities; 4. The challenge of recruitment and adherence; 5. The importance of homogeneity and proper quantification of rehabilitative strategies; and 6. Ethical issues. We are convinced that teaching the basics of scientific research in PRM could help physicians and therapists to choose a treatment based on (novel) scientific evidence. It may also promote scientific research in PRM to develop novel and personalized rehabilitation strategies using rigorous methodologies and randomized or benchmarking controlled trials in order to improve patients’ management.